Author Correction: Why rankings of biomedical image analysis competitions should be interpreted with care - Lena Maier-Hein (Nature Portfolio, 2019)
In the original version of this Article the values in the rightmost column of Table 1 were inadvertently shifted relative to the other columns. This has now been corrected in the PDF and HTML versions of the Article.